Graduate Teaching Assistant Opinions on Balance of Teaching and Professional Training (Journal of Education and Development, 2018)
This study was designed to determine the experience of graduate teaching assistants (GTAs) in programs that provide educational training in teaching and professional practice. Because this study involves investigational research, qualitative approaches were used, including interviews with ten teaching assistants working with educational faculty in Najran University. Content analysis, a qualitative data analysis method, was used. GTAs reported on the teaching programs and professional practices needed to fulfill their training requirements and the balance between teaching standards and quality performance, in terms of evaluation, advancement, training programs, and opportunities available in teaching departments. Overall, GTAs were not satisfied with their teaching training programs. The responses were in consensus that GTAs desired more time to learn professional teaching skills, and that they would like more observation and evaluation of their performance. Seeking the opinions of GTAs regarding teaching training programs will not only enhance their experience, but also could improve the education that they provide to students.